2018
DOI: 10.5114/hivar.2018.73359
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related stigma experienced by people living with HIV/AIDS in coastal South India

Abstract: Introduction: The present study assessed the human immunodeficiency virus (HIV)-related stigma and the factors influencing it among people living with human immunodeficiency virus (PLHIV) in tertiary care hospitals at Mangalore, South India. Stigma related to HIV still persists as a major public health issue globally and varies from person to person. The various forms of HIV-related stigma are personalized stigma, disclosure stigma, negative self-image stigma, and public attitude stigma. Material and methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…Specifically, women living with HIV may be more susceptible to HIV discrimination as a result of being subjected to gender, caste discrimination, and having fewer economic resources. This finding is in line with another outcome revealing that discrimination was higher among women as homemakers, who were generally confined to their homes [21,24]. Education was associated with discrimination, this is consistent with previous studies among PLWHA [22,24,26], in which high education level and financial difficulties were associated with greater perceived discrimination.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Specifically, women living with HIV may be more susceptible to HIV discrimination as a result of being subjected to gender, caste discrimination, and having fewer economic resources. This finding is in line with another outcome revealing that discrimination was higher among women as homemakers, who were generally confined to their homes [21,24]. Education was associated with discrimination, this is consistent with previous studies among PLWHA [22,24,26], in which high education level and financial difficulties were associated with greater perceived discrimination.…”
Section: Discussionsupporting
confidence: 92%
“…The findings revealed that age, gender, marital status, occupation, public health concerns, and negative self-image were statistically significant in overall stigma (p < 0.05). In the multivariate logistic regres- vents HIV interventions as most of HIV interventions target younger groups considered to be at higher risk [21,23,24]. The feeling of guilt and low self-esteem among PLWHA as they grow old, isolation from families and communities increase the risk of getting stigmatized [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations